Correlation of Human Mobility in Capitals of Seven European Countries During the COVID-19 Pandemic - Predrag Katanić; Srdjan Damjanović (Operational Research in Engineering Sciences: Theory and Applications, 2022)
We monitored and compared human mobility for six discrete categories during two year the COVID-19 pandemic in seven European countries: Austria, France, Italy, United Kingdom, Serbia, Spain, and Sweden, and their capitals: Vienna, Paris, Rome, London, Belgrade, Madrid and Stockholm. We have chosen countries whose capitals have more than a million inhabitants and which are located in various parts of Europe. We chose Sweden because it had a policy with the mildest restrictions on population movement during the pandemic. The collected data for the time period from February 15, 2020 until February 11, 2022. Using basic statistical methods, we found that there is a high degree of correlation between the data, which represent the mobility of people across the countries and the mobility of people in the capital of all seven observed European countries for six discrete categories. Based on this, it can be concluded that the mobility of people during the COVID-19 pandemic differs a lot from country to country, because the policies of governments in restricting the movement of people in the past two years have also differed significantly. Through this we want to show that data from Google Community Mobility Reports can be combined with many other data from various areas of human life and work and that various statistical processing of these data can be done to show various types of correlations with human mobility during the COVID-19 pandemic and how it affects the lives and economies of people around the world.